2019
DOI: 10.3928/1081597x-20190916-01
|View full text |Cite
|
Sign up to set email alerts
|

Intracorneal Ring Segments Implantation Outcomes Using Two Different Manufacturers' Nomograms for Keratoconus Surgery

Abstract: PURPOSE: To compare the outcomes of intracorneal ring segments (ICRS) implantation in keratoconic eyes with a similar tomographic pattern, using two different manufacturers' nomograms for surgical planning. METHODS: ICRS were implanted alternately in patients with the same tomographic pattern of keratoconus divided into two groups according to the surgical planning proposed by the ICRS manufacturers (Keraring, Mediphacos, Belo Horizonte, Brazil, and Fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In 2 studies regarding ICRS for keratoconus, these values were higher for CI and lower for IOS, indicating better outcomes than in postkeratoplasty eyes. 42,43 Nevertheless, our results improved after PRK, with mean CI significantly rising to 0.77 and 0.81, whereas the mean IOS decreased to 0.48 and 0.36 for corneal and refractive astigmatism, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…In 2 studies regarding ICRS for keratoconus, these values were higher for CI and lower for IOS, indicating better outcomes than in postkeratoplasty eyes. 42,43 Nevertheless, our results improved after PRK, with mean CI significantly rising to 0.77 and 0.81, whereas the mean IOS decreased to 0.48 and 0.36 for corneal and refractive astigmatism, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…3 Change in corneal tomography pattern with single ring implantation in a patient with asymmetric cone although the nomogram recommended double ring implantation Fig. 4 Change in corneal tomography pattern with double ring implantation in a patient with central cone and improves CDVA [12]. Recent evidence suggests that normalization of the corneal asphericity [4] has a role in visual improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rocha et al ( 2019 ) compared the Keraring and Ferrara ring nomograms, and concluded that the Keraring nomogram yielded better improvements in the topographic cylinder. However, our QN performed better in reducing the topographic cylinder than the SN, although the postoperative differences between both nomograms were not statistically significant (p = 0.29).…”
Section: Discussionmentioning
confidence: 99%
“…Intracorneal ring segment (ICRS) implantation flattens the central corneal curvature, thus reducing the refractive error and keratometry values, as well as improving visual outcomes (Kymionis et al 2014 ; Tian et al 2018 ; Iqbal et al 2019c ). Keraring segments (Mediphacos Inc., Belo Horizonte, Brazil), Ferrara ring segments (AJL Ophthalmic S.A., Vitoria‐Gasteiz, Spain) and INTACS ring segments (Addition Technology, Inc., Lombard, IL, USA) are widely used to correct refractive status in keratoconus patients, regularizing the anterior corneal surface to decrease both myopic and astigmatic components (Saleem 2015 ; Heikal et al 2017 ; Guyot et al 2019 ; Rocha et al 2019 ; Zaky et al 2020 ). The introduction of femtosecond laser surgery increased the popularity of ICRS implantation among cornea surgeons, as the procedure is simple, safe and accurate (Ibrahim et al 2016 ; Al‐Tuwairqi et al 2017 ; Park et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%